Perilaku Struktural Gable Frame Baja dengan Variasi Bentang, Jumlah Portal dan Kelas Situs pada Daerah Risiko Gempa Besar - Sulendra, I.K.; Listiawaty, H.; Sutrisno, M. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Limited land area and cross-sectional of steel profiles make planners have to choose the type of structure that is effective and efficient. Variations in the type of subgrade during an earthquake will give a different response to the structure which ultimately determines the dimensions of the structural elements. This study aims to determine the behavior of gable frame structures with variations in spans, number of portals and site classes. Modeling is done with variations of portal spans of 8, 24, and 30 m. The second variation is the number of portals, namely 1, 2 and 3 portals with a span of 24 m. The 3rd variation is in the form of class sites (hard, medium and soft soil) with a span of 2x24 m. The behavior analyzed is the base shear force, roof displacement and the demand to capacity ratio of the column and rafter. The 18 m span uses the IWF profile 200x150x6x9, the 24 m span uses the 300x150x6.5x9 profile and the 30 m span uses the 350x175x9x12 profile. The ratio of demand to capacity respectively for the column structure is 0.1909; 0.2560 and 0.2494 for spans of 18, 24 and 30 m. In the variation of the number of portals, it was found that designs 1, 2 and 3 had a Demand-Capacity Ratio value of 0.687 for rafters; 0.639 and 0.638 while in the column obtained respectively 0.713; 0.873 and 0.915. The design of the number of portals 1, 2 and 3 has a maximum deviation value of 68,699; 78,364 and 82,462 mm. In terms of serviceability, it shows a larger deviation and increases its capacity in resisting bending and compression. The results of the analysis of the 3 models with variations in soil sites show that hard soil, medium soil and soft soil have base shear force values of 205,163 kN, 337,883 kN, and 269,899 kN and the maximum deviation at the top of the building is 61,981 mm, 102,079 mm, and 37,642 mm.